2021
DOI: 10.1101/2021.07.16.452643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Huntington’s disease age at motor onset is modified by the tandem hexamer repeat in TCERG1

Abstract: Background: Huntington's disease is caused by an expanded CAG tract in HTT. The length of the CAG tract accounts for over half the variance in age at onset of disease, and is influenced by other genetic factors, mostly implicating the DNA maintenance machinery. We examined a single nucleotide variant, rs79727797, on chromosome 5 in the TCERG1 gene, previously reported to be associated with Huntington's disease and a quasi-tandem repeat (QTR) hexamer in exon 4 of TCERG1 with a central pure repeat. Methods: We d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…We also detected dysregulated splicing in the TCERG1 gene, a regulator of transcriptional elongation and pre-mRNA splicing, in both IsoHD and HD striatum. TCERG1 has been identified as a genetic modifier of age of onset in HD, where the length of a quasi-tandem repeat (QTR) hexamer in exon 4 of TCERG1 is inversely correlated with age at the onset of symptoms 26,32 . In our results, we found that the decreased inclusion of an adjacent retained intron and exon 6 in the TCERG1 transcripts is associated with CAG length, although not monotonically.…”
Section: Discussionmentioning
confidence: 99%
“…We also detected dysregulated splicing in the TCERG1 gene, a regulator of transcriptional elongation and pre-mRNA splicing, in both IsoHD and HD striatum. TCERG1 has been identified as a genetic modifier of age of onset in HD, where the length of a quasi-tandem repeat (QTR) hexamer in exon 4 of TCERG1 is inversely correlated with age at the onset of symptoms 26,32 . In our results, we found that the decreased inclusion of an adjacent retained intron and exon 6 in the TCERG1 transcripts is associated with CAG length, although not monotonically.…”
Section: Discussionmentioning
confidence: 99%
“…The up-or downpointing orientation of the triangle indicates the direction of effect, and the triangle size reflects the SNV MAF. We previously described a delaying age at motor onset modifier effect (5BM1), tagged by rs79727797, and subsequently attributed modification to the length of a quasi-tandem hexamer repeat encoding a glutamine/alanine tract in TCERG1 (Lobanov et al, 2022). This SNV tag (red in Figure 1B) showed the greatest significance (age at motor onset: p=8.9E-14; age at TFC6: p=1.8E-18), but conditional analyses in the age at TFC6 GWAS revealed a second modifier haplotype of significant SNVs spanning TCERG1 (blue triangles in Figure 1B).…”
Section: Many Modifier Loci Display Multiple Distinguishable Effectsmentioning
confidence: 99%
“…Conditioning the age at TFC6 analysis on either of the two 5BM1 or 5BM2 tag SNVs increased the significance for the other, and simultaneously conditioning on both SNVs eliminated all suggestive significant signals. The 5BM2 modifier is not associated with length variation in the TCERG1 hexamer repeat, being present only on chromosomes with the most frequent repeat length (91% of alleles) in the exome data used previously to analyze 5BM1 (Lobanov et al, 2022). 5BM2 tag SNVs do not reveal significant expression quantitative trait locus (eQTL) or splicing quantitative trait locus (sQTL) signals in brain in the GTEx database (https://www.gtexportal.org/home/aboutAdultGtex).…”
Section: Many Modifier Loci Display Multiple Distinguishable Effectsmentioning
confidence: 99%